When X-Rays Do Not Work. Characterizing the Internal Structure of Fossil Hominid Dentognathic Remains Using High-Resolution Neutron Microtomographic Imaging - Zanolli, Clément; Schillinger, Burkhard; Kullmer, Ottmar; Schrenk, Friedemann; Kelley, Jay; Rössner, Gertrud E.; Macchiarelli, Roberto (Frontiers in Ecology and Evolution, 2020)
The internal structure of the bones and teeth of extinct primates holds a significant amount of valuable paleobiological information for assessing taxonomy, phylogenetic relationships, functional, dietary and ecological adaptive strategies, and reconstructing overall evolutionary history. Technologies based on X-ray microfocus (X-µCT) and synchrotron radiation (SR-µCT) microtomography are increasingly used to noninvasively and non-destructively investigate the endostructural properties of fossil mineralized tissues. However, depending on the taphonomic dynamics that affected the specimens following deposition, and on the nature of diagenetic processes, X-µCT and even SR-µCT may provide only faint or no contrast between the mineralized tissues, thus complicating or inhibiting the study of structural features. Using a diverse sample of dentognathic hominid specimens from continental Asia, East Africa and Indonesia, chronologically ranging from the Late Miocene to the Early-Middle Pleistocene, we present examples of the successful application of another imaging technology, neutron microtomography (n-µCT), for the extraction, 3D rendering and quantitative assessment of internal morphological detail. The specimens were scanned at the ANTARES Imaging facility (SR4a beamline) at the FRM II reactor of the Technical University of Munich, Germany, at energies ranging from 3 to 25 meV. The datasets were reconstructed with a voxel size from 20 to 27 µm, i.e., at resolutions directly comparable to the X-ray-based microtomographic records commonly used in paleobiological studies of fossil primate remains. Our analyses focused on a mandible, SNSB-BSPG 1939 X 4, representing the Late Miocene hominid Sivapithecus from the Siwaliks of Pakistan; the early Early Pleistocene (Gelasian) partial mandible HCRP-U18-501 from Malawi, among the earliest specimens attributed to the genus Homo; and an assemblage of hominid dentognathic specimens from the Early-Middle Pleistocene deposits of the Sangiran Dome, Indonesia. While X-ray-based imaging revealed from low to moderate internal contrasts for the specimen of Sivapithecus, or from extremely poor to virtually no contrast for the Pleistocene remains from East Africa and Indonesia, the application of n-µCT produced sufficient differences in contrast to distinguish between tooth tissues on the one hand, and between cortical and trabecular bone on the other, thus enabling reliable qualitative and quantitative assessments of their characteristics.